Certain Aspects of the Analysis of Cryptocurrency Transactions during the Prevention and Investigation of Crimes (Law and Safety, 2021)
The analysis of separate tools for the visualization of movement of cryptocurrency values, and also identification of users who carried out the corresponding transactions has been carried out. The advantages and disadvantages of cryptocurrency from the point of view of offenders and law enforcement agencies have been studied. The main directions of using cryptocurrency in a criminal environment have been determined. The current state and perspectives of normative and legal regulation of cryptocurrency in Ukraine have been analyzed. Theoretical principles of cryptocurrency functioning have been studied. The basic concepts used in this area have been revealed. The properties of cryptocurrency have been described. The mechanism of its issuance of guaranteeing pseudo-anonymity while working with cryptocurrency has been outlined. Some features of blockchain technology and formation of cryptocurrency addresses have been revealed. It has been noted that one of the first and most well-known cryptocurrency is bitcoin. The format of bitcoin address presentation has been described. It has been emphasized that bitcoin wallet software can operate with any number of addresses or each address can be served by a separate wallet. The technology of mixing transactions and the method of increasing the anonymity of CoinJoin have been described. The authors have revealed the possibilities of separate services intended for the analysis of cryptocurrency transactions (Maltego, Bitconeview, Bitiodine, OpReturnTool, Blockchain.info, Anyblockanalytics.com, Chainalysis, Elliptic, Ciphertrace, Blockchain Inspector). The process of risk assessment and construction of visual chains of cryptocurrency transactions has been demonstrated on the example of the “Crystal Expert” service. Different types of bitcoin addresses’ holders and risk levels have been described. The main and additional investigation tools used on the “Crystal Expert” platform have been revealed. Based on the conducted analysis, the authors have defined the main tasks for law enforcement agencies at the current stage of development of cryptocurrency. The basic requirements for tools designed for cryptocurrency analysis have been outlined. The authors have suggested some measures of law enforcement agencies’ respond to threats related to cryptocurrency.
Keywords: cryptocurrency; analysis of transactions; visualization; law enforcement agencies; crime prevention